Quality of life reporting in the management of posterior fossa tumours: A systematic review - Adegboyega, Gideon; Jordan, Chloe; Kawka, Michal; Chisvo, Nathan; Toescu, Sebastian M.; Hill, Ciaran (Frontiers in Surgery, 2022)
Introduction Survival amongst posterior fossa tumour (PFT) patients is improving. Clinical endpoints such as overall survival fail to depict QoL. There is yet to be a review of current QoL instruments used for adult PFTs. Aim of this review is to outline the QoL reporting in the management of PFTs and measure participation level. Methods This systematic review was conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analysis. A search strategy to identify adult patients with PFTs who took part in QoL metrics was conducted. Observational and experimental studies published from 1990 to date were included. Studies with a sample size less than 10 and performance measures such as Karnofsky Performance Status were not considered. Results A total of 116 studies were included in the final analysis. Vestibular schwannomas were the most common tumour pathology (n = 23,886, 92.6%) followed by pilocytic astrocytomas (n = 657, 2.5%) and meningiomas (n = 437, 1.7%)Twenty-five different QoL measures were used in the study pool. SF-36 was the most common (n = 55, 17 47.4%)QoL metric in the whole study pool, followed by the Penn Acoustic Neuroma QoL scale (n = 24, 20.7%) and Dizziness Handicap Inventory (n = 16, 13.8%). Seventy-two studies reported less-than 100% participation in QoL evaluation. The commonest reason for non-participation was a lack of response (n= 1718, 60.8%), incomplete questionnaires (n = 268, 9.4%) and cognitive dysfunction (n = 258, 9.1%). Conclusion Informed clinical decision-making in PFT patients requires the development of specific QoL outcomes. Core outcome sets, and minimal clinically important differences (MCID) are essential for these metrics to show clinically significant improvements in patient QoL. Word Count: 250